Athletes with disabilities in the Paralympic Games: a framing analysis of television news. Issue 4 (4th July 2017) - Kim, Kyoung T.; Lee, Soonhwan; Oh, Eung-Soo
ABSTRACT: The current study is intended to examine how mass media, especially TV news transcripts, have framed the Paralympic games and athletes with disabilities in their coverage of these events. A total of 283 United States TV news transcripts of broadcasts covering the Paralympic events held during the 25-year period between 1988 and 2012 were analysed in terms of three aspects of framing: (a) the types of issues covered, (b) the sources of information cited, and (c) the manner in which either episodic or thematic stories were employed. The results of the current study reveal that issues of optimism were the most commonly highlighted, athletes with disabilities were the most frequently cited sources of information, and episodic framing was the most commonly employed style in TV news transcripts of the Paralympic Games. The results yielded insight on how news networks have framed the Paralympic Games.